2020
DOI: 10.1016/j.isci.2020.101513
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inhibitory Receptors on T and NK Cells Defines Immunological Phenotypes of HCV Patients with Advanced Liver Fibrosis

Abstract: Summary Chronic HCV can result in advanced liver disease, including cirrhosis. Patients with advanced fibrosis experience poor clinical outcomes and increased risk for hepatocellular carcinoma (HCC). These outcomes are, in part, a consequence of immune dysfunction. Increased inhibitory receptor and Galectin-9 (GAL-9) expression is a possible mechanism promoting lymphocyte dysfunction. In this study, we measured the expression of inhibitory receptors and GAL-9 on T/NK cells of patients with chronic H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Blockade of TIGIT [ 128 ] and TIM3 [ 129 ], inhibitory molecules expressed by NK cells, is known to improve NK cell cytotoxicity against tumours. These molecules are also highly expressed on NK cells in HCV patients with advanced liver fibrosis, indicating that blockade, in this instance, may restore NK cell functionality and protection [ 130 ].
Fig.
…”
Section: Nk Cell Based/targeted Therapies For Liver Diseasementioning
confidence: 99%
“…Blockade of TIGIT [ 128 ] and TIM3 [ 129 ], inhibitory molecules expressed by NK cells, is known to improve NK cell cytotoxicity against tumours. These molecules are also highly expressed on NK cells in HCV patients with advanced liver fibrosis, indicating that blockade, in this instance, may restore NK cell functionality and protection [ 130 ].
Fig.
…”
Section: Nk Cell Based/targeted Therapies For Liver Diseasementioning
confidence: 99%
“…In the current study, the proportion of NKG2A + NK cells was elevated in the peripheral blood of CHB patients and significantly elevated in patients with active CHB, which is consistent with our previous findings ( 8 ). Recently, the expression of Gal-9 in NK cells has also been reported, and a high frequency of Gal-9 + NK cells was shown to reduce the effector capacity of NK cells ( 28 , 29 , 40 ). Gal-9 is widely expressed in a variety of human and mouse immune cells and exists in various sites including the cell membrane, cytoplasm, and nucleus ( 26 ).…”
Section: Discussionmentioning
confidence: 98%
“…Gal-9 is widely expressed in a variety of immune and non-immune cells and exists in the membranes, cytoplasm, and nuclei (25,26). The expression of Gal-9 on NK cells has been reported, and studies show that Gal-9 + NK cells are associated with decreased granzyme B, perforin, and granulysin production (27)(28)(29). During chronic viral infection, TIM-3 is continuously expressed on exhausted T cells (30).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced liver fibrosis have an increased risk of developing HCC, and this may be associated with the co-expression of multiple inhibitory receptors. 28 How the increased expression of the negative regulators of immune activation in the liver and spleen of patients with PH, including PD-1/Tim-3 and their ligands, as well as CD80 and CD86, may affect susceptibility to HCC remains to be clarified. Our previous study showed that the modulation of cytokine expression following splenectomy may reduce the risk of HCC development in HBV-related cirrhotic patients with PH.…”
Section: Discussionmentioning
confidence: 99%